(untitled) (London, 1993)
Bacterial diseases are among the most important causes of losses among fish stocks. A full understanding of the aetiological agent, the pathogenesis, biochemistry, antigenicity, epizootiology and the inter-relationship of stress-related and environmental factors is essential for successful management and control. This book, which has been written as a standard text for students of aquaculture, veterinarians and microbiologists, brings these aspects together and reflects current international practices and incidence.
Keywords: Fish; Diseases